West Nile virus encephalomyelitis in horses in Ontario: 28 cases - Weese, J. Scott (2003)
West Nile virus encephalomyelitis was diagnosed in 28 horses presented to the Ontario Veterinary College Veterinary Teaching Hospital between August 20 and October 15, 2002. The age range of affected horses was 5 months to 20 years (mean 6.9 years, median 6 years). Clinical signs were highly variable. Duration of hospitalization ranged from < 1 to 12 days (mean 5 days, median 5.4 days). Overall, 16 of the 28 (57%) horses were discharged and, of the 14 from which follow-up information was available, 13 (93%) were reported to be clinically normal 4 to 6 weeks following discharge, while the other horse had markedly improved. This pathogen is emerging as an important cause of neurological disease in Canada.